Perceived Social Presence and Online Purchase Intentions: Mediating Role of Perceived Safety - Pham, Mai Thi Ngoc; Tran, Hung Van (Journal of Posthumanism, 2025)
This study investigates the impact of perceived social presence on online purchase intention, focusing on the mediating roles of perceived safety, perceived risk, and trust. The theoretical foundation integrates the social presence theory, the theory of cognition, the rational action theory, and the technology acceptance model. A mixed-method approach was adopted, with qualitative research refining measurement scales and quantitative research validating the model through linear structural analysis of survey data from 239 online shoppers. The findings reveal that perceived social presence significantly influences purchase intention, with safety, risk, and trust playing confirmed mediating roles. The results underscore the importance of enhancing perceived social presence, safety, and risk management in online stores to foster trust and drive purchase intentions.